Improving Students’ Speaking Skill By Using Show And Tell Method: A Classroom Action Research - betty kasita bangun (Universitas Jambi, Magister Program of English Education Department, 2018)
This research employed a qualitative study using a Classroom Action Research approach by Kemmis and Mc. Taggart which was done during 3 cycles. Each of the cycle consists of four phases; planning, acting, observing, and reflecting, while each cycle was done in two meetings. Data were collected through the observation sheet, field notes, interview and and tests. The research findings show that there were improvement on students’ speaking skill. In cycle one, the process of teaching learning with Show and Tell Method suggested a potential improvement, the researcher found some minor technical problems and weaknesses that leave rooms for improvement. Afterward, necessary alterations and revisions were done and later applied in cycle two and three. The result of the research suggested that the students show a tremendous improvement during the process of teaching learning when Show and Tell Method was applied. The students’ participation and vocabulary mastery were increased; they were more active, enthusiastic, and confident in speaking.